Pemanfaatan Lahan Sempit Melalui Urban Farming Sebagai Upaya Mewujudkan Kemandirian Pangan Keluarga - Ivan Sanjiva Redy; Sri Subekti; Lenny Luthfiyah (AGRIFITIA : Journal of Agribusiness Plantation, 2026)
Rapid urbanization in Surabaya City has led to the conversion of agricultural land into residential areas, thus threatening food security. To address this, the Surabaya City Government, through the Department of Food Security and Agriculture, is promoting an urban farming program as a solution for utilizing limited land in urban areas. Various urban farming studies generally focus on partial crop cultivation, while studies on the integration of agriculture, fisheries, and livestock on a micro-scale in urban areas are still limited. This study aims to describe the utilization of limited land based on multi-sector integration implemented by the Mekarsari Farmers Group in Baratajaya Village, Gubeng District, Surabaya City, and to determine the benefits of urban farming. The study used a qualitative descriptive approach with observation, in-depth interviews, and documentation techniques. The results showed that the group developed an integrated urban farming model through a combination of crop cultivation (hydroponics, potted plants, tabulapots, and direct planting), fisheries (tarpaulin ponds, cement ponds, and biofloc drum systems), and household-scale livestock farming on limited land such as yards, building gaps, and rooftops. These findings demonstrate that multi-sector integration in urban micro-farms can increase household food availability, increase income, and strengthen family food security in a sustainable manner. The contribution of this research lies in the development of an integrated urban farming model that adapts to space constraints in dense urban areas.   ABSTRAKUrbanisasi yang pesat di Kota Surabaya menyebabkan terjadinya alih fungsi lahan pertanian menjadi kawasan permukiman, sehingga mengancam ketahanan pangan. Untuk mengatasi hal tersebut, Pemerintah Kota Surabaya melalui Dinas Ketahanan Pangan dan Pertanian menggalakkan program urban farming sebagai solusi pemanfaatan lahan sempit di wilayah perkotaan. Berbagai studi urban farming umumnya berfokus pada budidaya tanaman secara parsial, sementara kajian mengenai integrasi pertanian, perikanan, dan peternakan pada skala lahan mikro perkotaan masih terbatas. Penelitian ini bertujuan untuk mendeskripsikan pemanfaatan lahan sempit berbasis integrasi multisektor yang diterapkan oleh Kelompok Tani Mekarsari di Kelurahan Baratajaya, Kecamatan Gubeng, Kota Surabaya, serta mengetahui manfaat urban farming. Penelitian menggunakan pendekatan deskriptif kualitatif dengan teknik observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa kelompok mengembangkan model urban farming terintegrasi melalui kombinasi budidaya tanaman (hidroponik, tasapot, tabulapot, dan tanam langsung), perikanan (kolam terpal, kolam semen, drum sistem bioflok), serta peternakan skala rumah tangga pada lahan terbatas seperti halaman, sela bangunan, dan atap rumah. Temuan ini menunjukkan bahwa integrasi multisektor pada lahan mikro perkotaan mampu meningkatkan ketersediaan pangan rumah tangga, menambah pendapatan, serta memperkuat ketahanan pangan keluarga secara berkelanjutan. Kontribusi penelitian ini terletak pada pengembangan model urban farming terintegrasi yang adaptif terhadap keterbatasan ruang di kawasan padat perkotaan.